The Effect of Cognitive Behavioral Therapy in Patients with Psychosis and Schizophrenia: A Systematic Review - Petrus Ordianus Wilson Laru; Hanik Endang Nihayati; Dian Tristiana (GLOBAL HEALTH SCIENCE GROUP, 2025)
To investigate the effect of cognitive behavioral therapy in patients with psychosis and schizophrenia. CBT plays a crucial role as an effective therapy in addressing psychotic disorders and schizophrenia by altering cognitive and behavioral patterns, reducing psychotic symptoms, enhancing self-control abilities, addressing cognitive dysfunction, and improving the overall quality of life of patients.Method: A systematic review of the effectiveness of psychological interventions in treating psychosis and schizophrenia focused on cognitive therapy has been conducted. The electronic databases Springer, Science Direct, Proquest, and Clinical Trials were searched using a combination of different search terms. Data were independently extracted by one author, and a synthesis of the results was offered. We identified articles fulfilling inclusion criteria: articles that investigate and report the role of CBT in managing and reducing symptoms and disabilities related to schizophrenia. The majority of research has been cross-sectional and has shown that increased cognitive biases in comparison to healthy controls are associated with psychoses in schizophrenia. The search date was conducted in February 2024, and the search was re-run in March 2024 for new entries.Result: 10 papers were included and reported the effectiveness of cognitive behavioral therapy approach interventions in reducing psychosis. Ultimately, no reliable factors were definitively linked to better outcomes after cognitive therapy. Many potential influences were either not confirmed in other studies or based on weak research.Conclusion: Additionally, studies often examined these factors independently, ignoring their potential interconnectedness (like age and education). Moving forward, researchers need well-designed studies to explore the true impact of these potential factors on treatment response. Understanding these factors can help determine who benefits most from cognitive behavioral therapy and ultimately lead to better outcomes.